A Video-Game-Based Oral Health Intervention in Primary Schools-A Randomised Controlled Trial - Ahmad Aljafari; Rawan ElKarmi; Osama Nasser; Ala'a Atef; Marie Therese Hosey (MDPI AG, 2022)
Background: Poor oral health practices and high levels of dental caries have been reported among children in the developing world. Video games have been successful in promoting oral health in children. The aim of this study was to assess the impact of an oral-health-education video game on children's dietary knowledge and dietary and toothbrushing practices; Methods: Two Schools in Amman, Jordan were randomly selected and assigned to either intervention or control. Six- to eight-year old children took part. The intervention group played the oral-health-education video game; the control group received no intervention. The groups were compared in terms of changes in: child dietary knowledge, dietary and toothbrushing practices, plaque scores, and parental familiarity with preventive treatments. Data were submitted to statistical analysis with the significance level set at p ≤ 0.05. Results: Two hundred and seventy-eight children took part. Most (92%) had carious teeth. At baseline, children reported having more than one sugary snack a day and only 33% were brushing twice a day. Most parents were unaware of fluoride varnish (66%) or fissure sealants (81%). At follow-up, children in the intervention group had significantly better dietary knowledge, and parents in both groups became more familiar with fluoride varnish. There were no significant changes in children's plaque scores, toothbrushing and dietary practices, or parental familiarity with fissure sealants in either group. Conclusions: Using an oral-health-education video game improved children's dietary knowledge. However, future efforts should target children together with parents, and need to be supplemented by wider oral-health-promotion.